Sleep disorders in chronically dialyzed patients - Agnieszka Pluta; Alicja Marzec; Maria Budnik-Szymoniuk; Kamila Faleńczyk (Kazimierz Wielki University, 2018)
Sleep disorders are a significant problem in the dialysis patient population. They range from 30 to 80% of patients with kidney disease. Sleep submergers carry a wide range of consequences, both psychological and somatic. Obstructive sleep apnea, restless legs syndrome, excessive daytime sleepiness and insomnia are the most common sleep disturbances among dialysis patients. The aim of the study was to analyze the conditions and the most frequently occurring sleep disorders in patients with chronic kidney disease, dialyzed based on the subject literature review. Sleep disorders are both quantitative and qualitative. They carry numerous negative effects in the sphere of mental and somatic health of the patient, they decrease the overall quality of life. They heighten the already increased cardiovascular risk in the dialysis population. Therefore, early recognition and treatment of sleep disorders in dialysis patients is important. Periodic assessment of the sleep quality of a dialysis patient should be included in the therapy standard.